Why do students not complete a Masters in Family Medicine Degree? - M. Whitfield; S. Fehrsen (South African Family Practice)
Background: The Masters in Family Medicine Degree of the Medical University of Southern Africa is a distance, self-directed learning course that usually lasts between 3 and 5 years. Since starting in 1970-80, more students have failed to complete the course than have graduated. We wanted to understand the students' reasons for not completing the degree.